MSP-RON Pathway: Potential Regulator of Inflammation and Innate Immunity - Huang, Lingtong; Fang, Xueling; Shi, Danrong; Yao, Shuhao; Wu, Weifang; Fang, Qiang; Yao, Hangping (Frontiers in Immunology, 2020)
Macrophage-stimulating protein (MSP), a soluble protein mainly synthesized by the liver, is the only known ligand for recepteur d'origine nantais (RON), which is a member of the MET proto-oncogene family. Recent studies show that the MSP-RON signaling pathway was not only important in tumor behavior，but also participate in the occurrence or development of many immune system diseases. Activation of RON in macrophages results in the inhibition of nitric oxide synthesis as well as lipopolysaccharide (LPS)-induced inflammatory response. MSP-RON is also associated with chronic inflammatory responses, especially chronic liver inflammation, and might serve as a novel regulator of inflammation which may due to affect the metabolism in the body. Another study provided evidence of the relationship between MSP-RON and autoimmune diseases, suggesting a potential role for MSP-RON in the development of drugs for autoimmune diseases. Moreover, MSP-RON plays an important role in maintaining the stability of the tissue microenvironment and contributes to immune escape in the tumor immune microenvironment. Here, we summarize the role of MSP-RON in immunity, based on recent findings and lay the foundation for further research.